Potential Nutrients for Preventing or Treating Bronchopulmonary Dysplasia. (March 2017) - Ma, Liya; Zhou, Ping; Neu, Josef; Lin, Hung-Chih
Summary: Bronchopulmonary dysplasia (BPD) is a frequent complication occurring in extremely preterm infants. Despite recent advances in newborn medicine, the incidence of BPD does not appear to have changed markedly, and specific treatments and prevention strategies are still lacking. Nutrition plays an important role in normal lung development and maturation. Malnutrition may delay somatic growth and new alveoli development, thus aggravating pulmonary injury involved in the pathogenesis of BPD. However, few nutrients have been investigated for their potential to mitigate the pathogenesis of BPD. In this article, we reviewed the recent progress in research on potential nutrients useful for the prevention or treatment of BPD, including glutamine, cysteine and N-acetylcysteine, L-arginine and L-citrulline, long chain polyunsaturated fatty acids (LCPUFAs), inositol, selenium, and some antioxidant vitamins including vitamin A. Current evidence shows that vitamin A and LCPUFA can prevent BPD, and that L-citrulline might provide a new method to treat chronic pulmonary hypertension associated with BPD in premature infants. The effects of other nutrients on BPD prevention need to be further studied.